Investigadores de mayor visibilidad en Organización y Representación del Conocimiento: un estudio desde el análisis de cocitaciones - Oliveira, Ely Francina Tannuri de [UNESP]; Grácio, Maria Cláudia Cabrini [UNESP]; Silva, Ana Claudia Cardoso da [UNESP] (My University, 2010)
The most visible researchers in Knowledge Organization and Representation were identified, from the perspective of Brazilian researchers, based on cocitations from the papers presented in the last five meetings of the Encontros Nacionais de Pesquisa of the Associação Nacional de Pesquisa e Pós- Graduação em Ciência da Informação (ENANCIBs) from 2003 to 2008. First, the total number of references was identified, a total of 134 articles. Second, a citation analysis was conducted, being considered the most cited authors those who received 12 citations or more, which resulted in 31 most cited authors. Third, the Pajek software was used for the construction of the co-citation network and, thereafter, some indicators were calculated with the Ucinet software, which describe the structure and cohesion of the generated network, and, particularly, its density, and its degree of centrality, betweenness and proximity. The high cohesion of the network and the compliance between the most co-cited authors and the calculated indicators were verified.

Se identifican los investigadores con mayor visibilidad en Organización y Representación del Conocimiento, desde el punto de vista de los investigadores brasileños, a partir de las cocitaciones realizadas en los artículos presentados en los cinco últimos Encontros Nacionais de Pesquisa da Associação Nacional de Pesquisa e Pós-Graduação em Ciência da Informação (ENANCIB), realizados entre 2003 y 2008. Se localizó el conjunto total de referencias, compuesto por 134 artículos y, realizado el análisis de citas, se consideraron como autores más citados a aquellos que hubieran recibido 12 citas o más: un total de 31. Seguidamente, se utilizó el software Pajek para la construcción de la red de cocitación y se calcularon, por medio del software Ucinet, algunos indicadores que describen la estructura y cohesión de la red generada, en particular su densidad y su centralidad de grado, de intermediación y de proximidad. Se verificó la alta cohesión de la red y la conformidad entre los autores más cocitados y los indicadores calculados.
Pesquisadores de maior visibilidade em Organização e Representação do Conhecimento: um estudo a partir da análise de cocitações
The most visible researchers in knowledge organization and representation: a co-citation study
Keywords: análise bibliométrica; análise de citação; análise de co-citação; ENANCIB; Organização e Representação do Conhecimento; rede de cocitação